1994
DOI: 10.1902/jop.1994.65.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Therapy in Young Adults With Severe Generalized Periodontitis

Abstract: This study evaluated the effect of periodontal therapy on clinical and microbiological parameters in 23 subjects with severe generalized early onset periodontitis. Therapy consisted of oral hygiene instruction and root planing and scaling, followed 3 months later by open flap debridement. Subjects were monitored for both clinical measures and levels of Actinobacillus actinomycetemcomitans and Porphyromas gingivalis as identified by indirect immunofluoresence. Clinical and microbiological evaluations were done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 22 publications
0
14
2
Order By: Relevance
“…Conversely, AP patients were selected only if there was evidence (from dental history and/or old radiographs) that the onset of the disease occurred under 35 years of age and that they were systemically healthy. Subjects with generalized aggressive periodontitis were defined, as previously described, as patients with > 5 mm of attachment loss at a minimum of one site in > 8 teeth, three of which were other than first molars and incisors (Gunsolley et al 1994). Only six of 18 patients with AP presented the generalized form.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, AP patients were selected only if there was evidence (from dental history and/or old radiographs) that the onset of the disease occurred under 35 years of age and that they were systemically healthy. Subjects with generalized aggressive periodontitis were defined, as previously described, as patients with > 5 mm of attachment loss at a minimum of one site in > 8 teeth, three of which were other than first molars and incisors (Gunsolley et al 1994). Only six of 18 patients with AP presented the generalized form.…”
Section: Methodsmentioning
confidence: 99%
“…Some previously published studies have even demonstrated that A. actinomycetemcomitans is a pathogen which is able to invade periodontal tissues but evade mechanical-chemical therapies (27,32,33). It is well established in the literature that A. actinomycetemcomitans-associated periodontitis requires periodontal therapy composed of a three-step strategy: (i) subgingival plaque control by mechanical debridement, (ii) administration of systemic antibiotics, and, as required, (iii) gingival flap surgery (14). Especially, the combination of metronidazole plus amoxicillin (amoxicilline) has been shown to improve the clinical and microbial parameters of patients infected with A. actinomycetemcomitans since it was first reported by van Winkelhoff et al (42).…”
mentioning
confidence: 99%
“…1996). The treatment of patients with advanced disease is difficult and the regeneration of lost tissue is challenging (Gunsolley et al. 1994, Gustke 1998).…”
mentioning
confidence: 99%